DESIGN AND PERFORMANCE ANALYSIS OF 5,8 GHZ CLOVERLEAF AND HELIX ANTENNA AS FIRST PERSON VIEW VIDEO RECEIVER IN DRONE RACING - Maulana, Rigo; Imansyah, Fitri; Yacoub, Redi Ratiandi (Faculty of Engineering, Universitas Tanjungpura, 2024)
First Person View (FPV) technology is used, where real-time video signals from drones are transmitted to ground stations, and provide a more realistic experience through FPV display through the monitor screen. This research focuses on designing and analyzing the performance of Cloverleaf and Helix antennas as FPV video receivers on Racing Drones with a frequency of 5,8 GHz which are capable of having a greater receiving power range from transmitters than the default antennas on FPV. The simulation results in CST Studio Suite 2019 show that the Cloverleaf antenna with a wire diameter of 1,5 mm and a bend angle of 105 ° has a VSWR value of 1.463, return loss of -14.508 dB and Gain of 10.74 dBi. While the Helix antenna diameter of 0,8 mm has a VSWR value of 1.081, return loss of -28.101 dB and Gain of 15.54 dBi. Testing on the monitor screen, both types of antennas have been successfully realized on the FPV video monitor screen and are able to capture real-time images from the transmitter on Drone Racing. The longest distance reached is 454 m for Cloverleaf antennas, 425 m for Helix antennas, and 374 m for Cloverleaf and Helix antennas combined. Cloverleaf and Helix antennas on monitors are better for near-medium ranges, but the signal decreases and can be lost at longer distances.